The nation state and beyond: governing globalization processes in the nineteenth and early twentieth centuries - Löhr, Isabella; Wenzlhuemer, Roland (Springer, 2013)
This book show that looking at the nation state from the perspective of global entanglements allows its interpretation as a dynamic and multi-layered structure that takes part in globalization processes, and plays various and at times even contradictory roles
Literaturangaben
Keywords: Geschichte 1858-1939; Aufsatzsammlung; Transnationalisierung; Globalisierung; Bildung; Technik; Wirtschaft; Nationalstaat